2020
DOI: 10.1016/j.ijid.2020.07.083
|View full text |Cite
|
Sign up to set email alerts
|

Palpebral anthrax, a rare though important condition in villagers: A case report and literature review

Abstract: The aerobic Gram-positive rod Bacillus anthracis can cause potentially lethal diseases affecting different organs. Localized eyelid inflammation is a rare presentation of cutaneous anthrax. This case report involves two patients with palpebral anthrax admitted to the oculoplastic ward of Feiz Eye Hospital, Isfahan, Iran. The patients had a history of close contact with animals. Clinical presentation included palpebral swelling and necrosis of the eyelids in both cases. The patients first underwent an appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…It has been suggested that bacterial culture results may turn negative 3–4 h after the use of systemic antibiotics. For differential diagnosis, furuncles, carbuncles, erysipelas, necrotizing cellulitis, and other necrotizing infective ulcers should be evaluated, and bacterial culture should be taken before starting antibiotic therapy [6, 8]. In our case, anthrax was detected in the wound culture of the lesion, and clinical findings confirmed the diagnosis of periocular anthrax.…”
Section: Discussionmentioning
confidence: 63%
“…It has been suggested that bacterial culture results may turn negative 3–4 h after the use of systemic antibiotics. For differential diagnosis, furuncles, carbuncles, erysipelas, necrotizing cellulitis, and other necrotizing infective ulcers should be evaluated, and bacterial culture should be taken before starting antibiotic therapy [6, 8]. In our case, anthrax was detected in the wound culture of the lesion, and clinical findings confirmed the diagnosis of periocular anthrax.…”
Section: Discussionmentioning
confidence: 63%
“…Previously published anthrax case reports mostly relied on culture and smear for diagnosis. 1 , 10–12 Here, we reported the first case of cutaneous anthrax diagnosed by mNGS. On the basis of the clinical features of this patient’s skin lesions, we considered the possibility of cutaneous anthrax.…”
Section: Introductionmentioning
confidence: 87%
“…It has been reported that the prevalence of complications decreases with early diagnosis and appropriate antibiotic treatment. [2,3] Anthrax is a rare zoonotic disease in humans caused by Bacillus anthracis. The most common form of this disease is cutaneous anthrax.…”
mentioning
confidence: 99%
“…[ 1 ] Cutaneous anthrax is most commonly seen in the head, neck, and upper extremities, and although palpebral involvement is rare, it has an important place in eyelid complications. [ 2 ] Palpebral anthrax accounts for only 4% of anthrax cases. In cases of palpebral anthrax, complications such as cicatricial ectropion, eschar formation, and lagophthalmia may develop despite treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation